Sources of Variability in Coagulation Factor Assays - Thompson, S G; Martin, J C; Meade, T W (Thrombosis and Haemostasis, 1987)
Estimates of the components of variation of a number of coagulation factor assays are presented and are compared with those for other haematological and biochemical variables. They have been derived from a study in which fourteen volunteers gave blood samples approximately bi-monthly for three years. The systematic between-batch variation w7as generally only a small component of the total variation. However, the proportion of the total variation due to differences between people ranged from about 15% in the case of two measures of antithrombin III to about 85% for cholesterol and haemoglobin. For factor VII activity and fibrinogen, the figure was just over 70%. These estimates of the components of variation are not generally available in the literature. In view of the increasing interest in the role of coagulation factors in the pathogenesis of arterial disease, estimates of this kind are needed both for the interpretation of observed relationships as well as for planning sample sizes for future studies.
Keywords: Coagulation factors; Components of variability